Two new Kukri Snake species (Colubridae: Oligodon) from the Nakhon Si Thammarat Mountain Range, and addition of O. ocellatus to the fauna of Thailand - Pauwels, Olivier S. G.; Thongyai, Kanokorn; Chantong, Pajapon; Sumontha, Montri (Zootaxa, 2021)
We describe two new Kukri snakes of the genus Oligodon from the Nakhon Si Thammarat Mountain Range, southern peninsular Thailand. Oligodon phangan sp. nov., endemic to Pha-Ngan Island, Surat Thani Province, is characterized by a maximal known SVL of 369.1 mm; 12 maxillary teeth, the posterior three enlarged; 17-17-15 dorsal scale rows; 163–166 ventrals; 33–42 divided subcaudals; a single anal; dorsal color brown with a pair of discreet paravertebral and lateral stripes; no dorsal or supracaudal bands, blotches or crossbars; background color of belly pinkish-orange; underside of tail immaculate. Oligodon promsombuti sp. nov., whose type-locality is Khao Phanom Wang, Surat Thani Province, is also found in Trang Province, and is characterized by a maximal known SVL of 552.7 mm; 12 maxillary teeth, the posterior three enlarged; 17-17-15 dorsal scale rows; 177 ventrals; 40 divided subcaudals; a single anal; deeply forked hemipenes lacking spines; dorsal color blackish brown with nearly indistinct paravertebral stripes; no dorsal or supracaudal blotches or crossbars; background color of belly ivory, heavily speckled with subrectangular blackish blotches. We tentatively allocate both new species to the informal Oligodon-cyclurus-group. They are the 5th and 6th Oligodon species endemic to Thailand. We add Oligodon ocellatus, so far known only from Cambodia, southern Laos and southern Vietnam, to the Thai fauna, based on a specimen from Chong Mek, Ubon Ratchathani Province.